KOMUNIKASI DALAM IMPLEMENTASI PROGRAM UJI KEMAHIRAN BERBAHASA INDONESIA (UKBI) DI BALAI BAHASA JAWA BARAT - Reyhan Rahadian; Candradewin Candradewin; Mas Dadang Enjat Munajat (JANE - Jurnal Administrasi Negara, 2022)
This research is the result of research on communication in the implementation of the Indonesian Language Proficiency Test (UKBI) program at the West Java Language Center. UKBI is a measuring test tool to measure a person's proficiency in good and correct Indonesian. This research was motivated by the existence of problems, namely, the promotion of the UKBI program carried out by the West Java Language Center was not comprehensive or evenly distributed, the existing facilities and infrastructure at the West Java Language Center were inadequate. The purpose of this study was to determine how communication is in the implementation of the UKBI program at the West Java Language Center. This study aims to determine communication in the implementation of the UKBI program so far. This study uses a qualitative approach with data collection techniques literature study and field study observations, interviews, documentation studies. The results of the study show that communication in the implementation of the UKBI program has been running but needs to be improved. Socialization carried out in several places or agencies is still not evenly distributed. This needs to be further improved so that the implementation of UKBI runs even better and achieves the target in accordance with the desired target. Penelitian ini merupakan hasil penelitian mengenai komunikasi dalam implementasi program Uji Kemahiran Berbahasa Indonesia (UKBI) di Balai Bahasa Jawa Barat. UKBI merupakan alat tes ukur untuk mengukur kemahiran seseorang dalam berbahasa Indonesia yang baik dan benar. Penelitian ini dilatarbelakangi dengan adanya permasalahan yaitu,  promosi program UKBI yang dilakukan oleh Balai Bahasa Jawa Barat belum menyeluruh atau merata, sarana dan prasarana yang ada di Balai Bahasa Jawa Barat ada yang belum memadai. Tujuan dari penelitian ini untuk mengetahui bagaimana komunikasi dalam implementasi program UKBI di Balai Bahasa Jawa Barat. Penelitian ini bertujuan untuk mengetahui komunikasi dalam implementasi program UKBI selama ini. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data studi pustaka dan studi lapangan observasi, wawancara, studi dokumentasi. Hasil penelitian menunjukkan komunikasi dalam implementasi program UKBI sudah berjalan namun perlu ditingkatkan. Sosialisasi yang dilakukan di beberapa tempat atau instansi masih belum merata. Hal itu perlu ditingkatkan lagi agar pelaksanaan UKBI berjalan lebih baik lagi dan mencapai target sesuai dengan target yang diinginkan.